2010
DOI: 10.1007/s10753-010-9200-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Oral Glucocorticoid Therapy on CD4+CD25+CD127- and CD4+CD25high T Cell Levels in Asthmatic Patients

Abstract: Our purpose was to evaluate the effects of short-term oral glucocorticoid (GC) treatment on frequencies of T cells with putative regulatory phenotype (namely, CD4+CD25+CD127- and CD4+CD25high) in patients with asthma exacerbations. In addition, we sought to determine frequencies of above T cell subsets in adult asthmatic patients in relation to disease severity and different treatment regimens. The analysis was performed in 62 patients with different stages of asthma and ten healthy controls. Polychromatic flo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Pathological sites in TBP and non‐diabetic TB patients contained large numbers of activated T‐cells and small numbers of Treg, so that the function of Teff was not negatively affected by Treg. This study also demonstrated that the CD4+CD25+ phenotype does not provide an indication of the actual frequency of immunosuppressive Treg 25 . Compared with the control subjects in this study, there was a high frequency of CD4+CD25+CD127− T‐cells in the peripheral blood of patients with active TB, indicating that overall immune function was suppressed in TB patients.…”
Section: Discussionmentioning
confidence: 56%
“…Pathological sites in TBP and non‐diabetic TB patients contained large numbers of activated T‐cells and small numbers of Treg, so that the function of Teff was not negatively affected by Treg. This study also demonstrated that the CD4+CD25+ phenotype does not provide an indication of the actual frequency of immunosuppressive Treg 25 . Compared with the control subjects in this study, there was a high frequency of CD4+CD25+CD127− T‐cells in the peripheral blood of patients with active TB, indicating that overall immune function was suppressed in TB patients.…”
Section: Discussionmentioning
confidence: 56%
“…It provides symptomatic relief and the regression of severe forms of disease and may also enable a reduction in the dose of maintenance glucocorticoids [ 18 , 19 ]. The high concentrations of glucocorticoids achieved by IV pulse appears to have a more immediate and profound effect on Treg cells compared to conventional oral treatment [ 48 ]. However, despite the clinical efficacy of pulse for the initial management of active SLE, this benefit is not maintained for prolonged periods [ 17 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, neither the cellular phenotype nor the prognosis of the pre-treated dogs was significantly different from that of the treatment-naïve patients, presumably because such drugs were administered on a limited number of occasions prior to sampling and would thus have had only minimal opportunity to impact the immune system. Recent studies of human patients receiving short-term glucocorticoid therapy have similarly shown no change in the frequency of peripheral Tregs [73], [74]. In view of the lack of impact of pre-treatment on these variables, all dogs of the respective B and T cell groups were considered together in our final analysis.…”
Section: Discussionmentioning
confidence: 99%